A kind of environmentally friendly ground film with high mechanical properties and preparation method thereof

Through the use of modified inorganic nano -composite fillers in polyethylene vectors, the problem of proneness and low mechanical properties of polyethylene mullasts can be solved, and high -intensity, high toughness and environmentally friendly high -powered performance and environmentally friendly plastic membranes are realized.

CN118878975BActive Publication Date: 2025-01-28SHANDONG QIXIN ENVIRONMENTAL PROTECTION MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411376059.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-28
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Polyethylene mulch is prone to cracking during use, has low mechanical properties, and is difficult to meet the demand for high strength and toughness in agricultural production.

Method used

The graphene and inorganic nanoparticles were used to modify the 7-alumin oxyxohide, combined with linear low-density polyethylene and low-density polyethylene, and prepared to modify the inorganic nano-composite fillers through ultrasonic dispersing and heating reactions to improve the gymoplastin. Mechanical performance.

Benefits of technology

It significantly improves the mechanical properties of polyethylene mosaic membranes, enhances its strength and toughness, extended the service life, while maintaining the characteristics of environmental protection and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure YSDJOXI8RPXKWGMCQOO9J5YJWLPRVNMW5NJW7WMX
    Figure YSDJOXI8RPXKWGMCQOO9J5YJWLPRVNMW5NJW7WMX
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer composite materials, and specifically relates to a high mechanical performance environmentally friendly ground film and a preparation method thereof. The high mechanical performance environmentally friendly ground film comprises the following components in parts by weight: 60-70 parts of linear low-density polyethylene, 10-20 parts of low-density polyethylene, 5-10 parts of modified inorganic nano-composite fillers, 0.1-2 parts of antioxidants, 0.1-2 parts of light stabilizers, and 0.1-2 parts of lubricants. The modified inorganic nano-composite filler is prepared by modifying graphene and inorganic nanoparticles with 7-octenyltrimethoxysilane. The long carbon chain olefin at one end of 7-octenyltrimethoxysilane has good compatibility with polyethylene, which improves the compatibility of the inorganic filler with polyethylene. At the same time, 7-octenyltrimethoxysilane can form a entangled structure between graphene and inorganic nanoparticles due to its long carbon chain structure, thereby improving the dispersion performance of graphene and inorganic nanoparticles in polyethylene; the prepared polyethylene ground film takes into account high rigidity and toughness, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, and particularly relates to an environmentally friendly ground film with high mechanical properties and a preparation method thereof. Background Art

[0002] Drought and water shortage are key issues restricting the development of agricultural production and environmental governance in my country. Film mulching technology is an effective and important technical measure to solve drought and water shortage. Agricultural mulch has the functions of moisture retention, heat preservation, insect resistance, disease prevention, and weed growth inhibition. It can maintain soil moisture, improve water utilization, and alleviate the problem of soil water shortage in arid and semi-arid areas. At the same time, it improves the growth environment of crops, is conducive to crop growth and development, and increases crop yields and agricultural benefits. Plastic mulch has developed rapidly since its introduction and has been widely used in agricultural production and cultivation, becoming the third largest agricultural input after fertilizers and pesticides.

[0003] Polyethylene is the most common polymer material for ground film. From the perspective of polymerization process, polyethylene can be divided into low-density polyethylene (LDPE), high-density polyethylene (HDPE), and linear low-density polyethylene (LLDPE). LDPE is usually produced by free radical polymerization under high temperature and high pressure. Low-density polyethylene film has the advantages of high transparency, high toughness, odorlessness, good sealing, easy processing and low price. It is a very popular packaging material with huge market demand. High-density polyethylene is a linear structure with much higher crystallinity than low-density polyethylene. Although high-density polyethylene has excellent mechanical and thermal properties, its aging resistance and environmental stress cracking resistance are relatively poor. Linear low-density polyethylene is formed by copolymerization of ethylene and a small amount of α-olefins. It has a short branched structure of two to four carbon atoms. LLDPE is non-toxic, tasteless, odorless, and milky white. Compared with HDPE, it has the advantages of high toughness, high gloss, and low temperature resistance; compared with LDPE, it has better toughness, tear resistance and environmental stress cracking resistance. Therefore, LLDPE products are widely used in acid, alkali, organic solvent and other environments. In addition, LLDPE film is stronger and more puncture-resistant than LDPE film, and is suitable for making ultra-thin films. Under the same strength requirements, the thickness can be reduced to 20%-25% of LDPE.

[0004] Polyethylene mulch is produced and used in large quantities due to its low cost, light weight, and good tensile yield properties. With the development of agriculture, the coverage area of ​​mulch has expanded, leading to a gradual increase in the demand for polyethylene mulch. However, polyethylene has the characteristics of low mechanical properties and easy rupture during use. Therefore, it is particularly important to improve the mechanical properties of polyethylene film, prevent the film from rupturing, or extend its service life. In recent years, there have been a lot of research on improving the performance of polyethylene film, but the research content either stays on single-layer polyethylene or only explores the process of multi-layer polyethylene, and lacks research on the functionalization of polyethylene film. Therefore, it is urgent to realize the functionalization preparation of polyethylene film, broaden the use of film, and improve the mechanical properties. Summary of the invention

[0005] The purpose of the present invention is to provide an environmentally friendly mulch film with high mechanical properties and a preparation method thereof, which has the characteristics of moisture retention, heat preservation and insect resistance of ordinary polyethylene mulch films, and also has the characteristics of high strength, high toughness, green environmental protection and high efficiency.

[0006] The high mechanical performance environmentally friendly ground film of the present invention comprises the following components in parts by weight:

[0007] 60-70 parts of linear low-density polyethylene, 10-20 parts of low-density polyethylene, 5-10 parts of modified inorganic nanocomposite filler, 0.1-2 parts of antioxidant, 0.1-2 parts of light stabilizer, and 0.1-2 parts of lubricant;

[0008] The modified inorganic nano composite filler is graphene and inorganic nano particles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nano particles and 7-octenyltrimethoxysilane is 1: (0.1-0.5): (0.1-0.5).

[0009] Filling with inorganic rigid particles is one of the technical methods for modifying polyethylene mulch. The rigidity and dimensional stability of polyethylene modified by inorganic rigid particles have been greatly improved, and the cost has been reduced to a certain extent, but at the same time, some physical and mechanical properties of the base resin have also been deteriorated, such as toughness and weather resistance. Simply adding inorganic rigid particles is difficult to take into account the rigidity and toughness of polyethylene mulch due to agglomeration.

[0010] Graphene has high strength, good toughness, and can be bent. Adding graphene to polyethylene mulch can solve the defect of low toughness of inorganic nanoparticles. However, there is a strong van der Waals force between graphene nanosheets, which makes it easy to agglomerate in the polymer matrix, which will reduce the performance of nanocomposites. Traditional coupling agents are mostly organic silanes, titanates, aluminates and other compounds with amphiphilic structures. The graphene treated with them is mostly combined with polyethylene in the form of surface adsorption, physical entanglement, van der Waals force, etc. For example, the common KH550 has a hydrolyzable silicon-containing group at one end and an amino group at the other end. As a polar group, the amino group has poor compatibility with polyethylene. Due to the poor interfacial bonding between the two phases, it is difficult to obtain better compatibility, resulting in a decrease in the performance of the filling material. In order to solve this problem, the present invention uses 7-octenyltrimethoxysilane (trimethoxy (7-octen-1-yl) silane, CAS No. 52217-57-9) with a long carbon chain structure as a modifier, one end of which has a long carbon chain and a double bond structure, and has extremely high compatibility with non-polar polymers. The existing technologies (CN115716959A, CN115232404A, CN115637002A, etc.) all use 7-octenyltrimethoxysilane to directly treat polymers for use as a compatibilizer, and there is no report on using 7-octenyltrimethoxysilane to directly modify inorganic materials. When 7-octenyltrimethoxysilane treats graphene and inorganic nanoparticles, silane is first hydrolyzed into silanol, and then the silanol group undergoes a dehydration reaction with the surface of graphene and inorganic nanoparticles to form a chemical bond; at the same time, the long carbon chain olefin at the other end of 7-octenyltrimethoxysilane has good compatibility with polyethylene, which improves the compatibility of inorganic fillers with polyethylene. Further, due to its long carbon chain structure, an appropriate amount of 7-octenyltrimethoxysilane can form an entangled structure between graphene and inorganic nanoparticles, thereby improving the dispersion performance of graphene and inorganic nanoparticles in polyethylene. Furthermore, when graphene and inorganic nanoparticles are ultrasonically dispersed in a solvent, nanoscale inorganic granular fillers can be dispersed between graphene sheets to prevent graphene from agglomerating during polymer melt processing, thus acting as a barrier agent.

[0011] Furthermore, the inorganic nanoparticles are at least one of nano-silicon dioxide, nano-titanium dioxide, nano-calcium carbonate, and nano-zinc dioxide.

[0012] Furthermore, the average particle size of the inorganic nanoparticles is 20-150 nm. The average particle size D50 is measured by laser scattering measurement. In particular, the particle size of the inorganic nanoparticles is 60-80 nm. If the particle size is too small, the agglomeration effect of the particles will be aggravated; if the particle size is too large, it will not only affect the mechanical properties of the ground film, but also fail to isolate the graphene sheets under the action of ultrasound, which is not conducive to the dispersion of graphene.

[0013] Furthermore, the specific preparation process of the modified inorganic nanocomposite filler is:

[0014] Graphene is dispersed in a solvent, and then inorganic nanoparticles and 7-octenyltrimethoxysilane are added, ultrasonically dispersed uniformly, heated for reaction, filtered, washed, and dried to obtain a modified inorganic nanocomposite filler. By ultrasonically modifying graphene and inorganic nanoparticles in a solution in advance, not only can the inorganic nanoparticles fully isolate the graphene, but also a proper entanglement structure can be formed between the particles and the graphene, thereby improving the dispersion stability of the graphene and the inorganic nanoparticles.

[0015] Furthermore, the solvent is a mixed solution of deionized water and ethanol; the reaction temperature is 40-50° C., and the reaction time is 1-2 h.

[0016] Furthermore, the antioxidant includes a primary antioxidant and an auxiliary antioxidant; the primary antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant.

[0017] Furthermore, the light stabilizer is at least one of UV944 and UV622.

[0018] Furthermore, the lubricant is at least one of oleamide, erucamide, polyethylene wax, calcium stearate, and zinc stearate.

[0019] Furthermore, the low-density polyethylene is 14-16 parts. LDPE has better softness, transparency and lower production cost than LLDPE, but its dosage cannot be too much, otherwise it will affect the mechanical properties of the ground film. There is no special limitation on LDPE and LLDPE. Specifically, LDPE can use the film grade LD151 of Yanshan Petrochemical; LLDPE can use PF-0218D of Nova Chemical.

[0020] The present invention also provides a method for preparing an environmentally friendly mulch film with high mechanical properties, comprising the following steps:

[0021] (1) Weigh each component according to the ratio and mix them evenly;

[0022] (2) Adding the mixed material to an extruder for blow molding to obtain an environmentally friendly mulch film with high mechanical properties; wherein the temperature of the extruder feeding section is 165-170°C, the temperature of the compression section is 180-200°C, the temperature of the plasticizing section is 180-200°C, and the temperature of the die section is 170-175°C.

[0023] Beneficial effects:

[0024] (1) When the present invention uses 7-octenyltrimethoxysilane to modify graphene and inorganic nanoparticles in a solvent, the long carbon chain olefin at one end of 7-octenyltrimethoxysilane has good compatibility with polyethylene, thereby improving the compatibility of the inorganic filler with polyethylene. At the same time, due to its long carbon chain structure, 7-octenyltrimethoxysilane can form an intertwined structure between graphene and inorganic nanoparticles, thereby improving the dispersion performance of graphene and inorganic nanoparticles in polyethylene. Moreover, when graphene and inorganic nanoparticles are ultrasonically dispersed in a solvent, nanoscale inorganic granular fillers can be dispersed between graphene sheets, thereby preventing graphene from agglomerating during polymer melt processing, thereby playing the role of a barrier agent.

[0025] (2) Compared with the existing agricultural mulch films in China, the mechanical properties of the mulch films obtained by the present invention are significantly improved. The production of environmentally friendly mulch films with high mechanical properties can be achieved on ordinary mulch film production equipment without the need for additional investment, which is simple and easy. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] In the description of the present invention, it should be noted that all terms (including technical terms and scientific terms) used in the present invention have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and should not be understood as limitations on the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this invention.

[0028] Among them, in the following examples and comparative examples, the specific preparation process of the modified inorganic nanocomposite filler is the same, which is:

[0029] Graphene is dispersed in a solvent, and then inorganic nanoparticles and 7-octenyltrimethoxysilane are added, ultrasonically dispersed evenly, heated for reaction, filtered, washed, and dried to obtain a modified inorganic nanocomposite filler; the solvent is a mixed solution of deionized water and ethanol in a volume ratio of 1:1; the reaction temperature is 45°C, and the reaction time is 2h.

[0030] The preparation method of the environmentally friendly mulch film with high mechanical properties comprises the following steps:

[0031] (1) Weigh each component according to the ratio and mix them evenly;

[0032] (2) The mixed material is added into an extruder for blow molding to obtain an environmentally friendly mulch film with high mechanical properties; wherein the temperature of the extruder feeding section is 165°C, the temperature of the compression section is 185°C, the temperature of the plasticizing section is 190°C, and the temperature of the die section is 175°C.

[0033] Example 1

[0034] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0035] 60 parts of linear low-density polyethylene, 14 parts of low-density polyethylene, 5 parts of modified inorganic nanocomposite filler, 0.1 parts of antioxidant, 0.1 parts of light stabilizer, and 0.1 parts of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV944; the lubricant is oleamide;

[0036] The modified inorganic nano composite filler is graphene and inorganic nano particles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nano particles and 7-octenyltrimethoxysilane is 1:0.1:0.1; the inorganic nano particles are nano calcium carbonate; and the average particle size of the inorganic nano particles is 60 nm.

[0037] Example 2

[0038] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0039] 70 parts of linear low-density polyethylene, 16 parts of low-density polyethylene, 10 parts of modified inorganic nanocomposite filler, 2 parts of antioxidant, 2 parts of light stabilizer, 2 parts of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV622; the lubricant is polyethylene wax;

[0040] The modified inorganic nano composite filler is graphene and inorganic nanoparticles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nanoparticles and 7-octenyltrimethoxysilane is 1:0.5:0.5; the inorganic nanoparticles are nano calcium carbonate; and the average particle size of the inorganic nanoparticles is 80 nm.

[0041] Example 3

[0042] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0043] 60 parts of linear low-density polyethylene, 16 parts of low-density polyethylene, 10 parts of modified inorganic nanocomposite filler, 0.1 parts of antioxidant, 2 parts of light stabilizer, and 0.1 parts of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV622; the lubricant is erucamide;

[0044] The modified inorganic nano composite filler is graphene and inorganic nano particles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nano particles and 7-octenyltrimethoxysilane is 1:0.1:0.5; the inorganic nano particles are nano calcium carbonate; and the average particle size of the inorganic nano particles is 80 nm.

[0045] Example 4

[0046] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0047] 62 parts of linear low-density polyethylene, 14 parts of low-density polyethylene, 6 parts of modified inorganic nanocomposite filler, 0.5 parts of antioxidant, 0.7 parts of light stabilizer, and 0.8 parts of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV944; the lubricant is erucamide;

[0048] The modified inorganic nano composite filler is graphene and inorganic nanoparticles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nanoparticles and 7-octenyltrimethoxysilane is 1:0.2:0.2; the inorganic nanoparticles are nano calcium carbonate; and the average particle size of the inorganic nanoparticles is 60 nm.

[0049] Example 5

[0050] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0051] 67 parts of linear low-density polyethylene, 16 parts of low-density polyethylene, 8 parts of modified inorganic nanocomposite filler, 1.5 parts of antioxidant, 1.4 parts of light stabilizer, and 1.6 parts of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV622; the lubricant is erucamide;

[0052] The modified inorganic nano composite filler is graphene and inorganic nano particles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nano particles and 7-octenyltrimethoxysilane is 1:0.4:0.3; the inorganic nano particles are nano calcium carbonate; and the average particle size of the inorganic nano particles is 80 nm.

[0053] Example 6

[0054] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0055] 66 parts of linear low-density polyethylene, 15 parts of low-density polyethylene, 7 parts of modified inorganic nanocomposite filler, 1 part of antioxidant, 1 part of light stabilizer, and 1 part of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV944; the lubricant is oleamide;

[0056] The modified inorganic nano composite filler is graphene and inorganic nanoparticles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nanoparticles and 7-octenyltrimethoxysilane is 1:0.3:0.3; the inorganic nanoparticles are nano calcium carbonate; and the average particle size of the inorganic nanoparticles is 60 nm.

[0057] Example 7

[0058] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0059] 66 parts of linear low-density polyethylene, 10 parts of low-density polyethylene, 7 parts of modified inorganic nanocomposite filler, 1 part of antioxidant, 1 part of light stabilizer, and 1 part of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV944; the lubricant is oleamide;

[0060] The modified inorganic nano composite filler is graphene and inorganic nanoparticles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nanoparticles and 7-octenyltrimethoxysilane is 1:0.3:0.3; the inorganic nanoparticles are nano calcium carbonate; and the average particle size of the inorganic nanoparticles is 60 nm.

[0061] Example 8

[0062] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0063] 66 parts of linear low-density polyethylene, 20 parts of low-density polyethylene, 7 parts of modified inorganic nanocomposite filler, 1 part of antioxidant, 1 part of light stabilizer, and 1 part of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV944; the lubricant is oleamide;

[0064] The modified inorganic nano composite filler is graphene and inorganic nanoparticles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nanoparticles and 7-octenyltrimethoxysilane is 1:0.3:0.3; the inorganic nanoparticles are nano calcium carbonate; and the average particle size of the inorganic nanoparticles is 60 nm.

[0065] Example 9

[0066] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0067] 66 parts of linear low-density polyethylene, 15 parts of low-density polyethylene, 7 parts of modified inorganic nanocomposite filler, 1 part of antioxidant, 1 part of light stabilizer, and 1 part of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV944; the lubricant is oleamide;

[0068] The modified inorganic nano composite filler is graphene and inorganic nanoparticles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nanoparticles and 7-octenyltrimethoxysilane is 1:0.3:0.3; the inorganic nanoparticles are nano calcium carbonate; and the average particle size of the inorganic nanoparticles is 20 nm.

[0069] Example 10

[0070] A high mechanical performance environmentally friendly ground film, comprising the following components in parts by weight:

[0071] 66 parts of linear low-density polyethylene, 15 parts of low-density polyethylene, 7 parts of modified inorganic nanocomposite filler, 1 part of antioxidant, 1 part of light stabilizer, and 1 part of lubricant; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:0.5; the light stabilizer is UV944; the lubricant is oleamide;

[0072] The modified inorganic nano composite filler is graphene and inorganic nanoparticles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nanoparticles and 7-octenyltrimethoxysilane is 1:0.3:0.3; the inorganic nanoparticles are nano calcium carbonate; and the average particle size of the inorganic nanoparticles is 150nm.

[0073] Comparative Example 1

[0074] The components and preparation process are substantially the same as those of Example 6, except that vinyltrimethoxysilane is used to replace 7-octenyltrimethoxysilane.

[0075] Comparative Example 2

[0076] The components and preparation process are substantially the same as those of Example 6, except that the mass ratio of graphene, inorganic nanoparticles, and 7-octenyltrimethoxysilane is 1:1:0.3.

[0077] Comparative Example 3

[0078] The components and preparation process are substantially the same as those of Example 6, except that the mass ratio of graphene, inorganic nanoparticles, and 7-octenyltrimethoxysilane is 1:0.3:1. The tensile load and elongation at break of Examples 1-10 and Comparative Examples 1-3 were tested in accordance with GB / T 13022-1991, and the results are shown in Table 1.

[0079]

[0080] As can be seen from Table 1, the present invention uses 7-octenyl trimethoxysilane to modify graphene and inorganic nanoparticles in a solvent, and the long carbon chain olefin at one end of 7-octenyl trimethoxysilane has good compatibility with polyethylene, which improves the compatibility of inorganic fillers with polyethylene. At the same time, 7-octenyl trimethoxysilane can form a entangled structure between graphene and inorganic nanoparticles due to its long carbon chain structure, thereby improving the dispersibility of graphene and inorganic nanoparticles in polyethylene. Moreover, when graphene and inorganic nanoparticles are ultrasonically dispersed in a solvent, nanoscale inorganic granular fillers can be dispersed between graphene sheets to prevent graphene from agglomerating during polymer melt processing, thereby playing the role of a barrier agent. Comparative Example 1 uses a short carbon chain silane coupling agent, which cannot form an entangled structure between graphene and inorganic nanoparticles, and the coupling agent has a low compatibility with polyethylene, and the improved performance is limited. Comparative Example 2 shows that the inorganic nanoparticles in the present invention are mainly used for isolation. When the amount is too much, the mechanical properties of the film will not be improved, but the film properties may be reduced due to agglomeration. In addition, since 7-octenyltrimethoxysilane has a long carbon chain structure and its cost is relatively high, its amount should be controlled, otherwise the filler may be difficult to disperse due to excessive entanglement of the long chain structure.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high mechanical performance environmentally friendly ground film, characterized in that: Contains the following components in parts by weight: 60-70 parts of linear low-density polyethylene, 10-20 parts of low-density polyethylene, 5-10 parts of modified inorganic nanocomposite filler, 0.1-2 parts of antioxidant, 0.1-2 parts of light stabilizer, and 0.1-2 parts of lubricant; The modified inorganic nanocomposite filler is graphene and inorganic nanoparticles modified by 7-octenyltrimethoxysilane; wherein the mass ratio of graphene, inorganic nanoparticles and 7-octenyltrimethoxysilane is 1:(0.1-0.5):(0.1-0.5); The inorganic nanoparticles are at least one of nano silicon dioxide, nano titanium dioxide, nano calcium carbonate, and nano zinc dioxide; The average particle size of the inorganic nanoparticles is 20-150 nm; The specific preparation process of the modified inorganic nanocomposite filler is as follows: The graphene is dispersed in a solvent, and then inorganic nanoparticles and 7-octenyltrimethoxysilane are added, ultrasonically dispersed evenly, heated for reaction, filtered, washed and dried to obtain a modified inorganic nanocomposite filler.

2. The high mechanical performance environmentally friendly ground film according to claim 1, characterized in that: The solvent is a mixed solution of deionized water and ethanol; the reaction temperature is 40-50° C., and the reaction time is 1-2 hours.

3. The high mechanical performance environmentally friendly ground film according to claim 1, characterized in that: The antioxidant comprises a main antioxidant and an auxiliary antioxidant; the main antioxidant is a hindered phenol antioxidant, and the auxiliary antioxidant is a phosphite antioxidant.

4. The high mechanical performance environmentally friendly ground film according to claim 1, characterized in that: The light stabilizer is at least one of UV944 and UV622.

5. The high mechanical performance environmentally friendly ground film according to claim 1, characterized in that: The lubricant is at least one of oleamide, erucamide, polyethylene wax, calcium stearate and zinc stearate.

6. The high mechanical performance environmentally friendly ground film according to claim 1, characterized in that: The low density polyethylene is 14-16 parts.

7. The method for preparing an environmentally friendly mulch film with high mechanical properties according to any one of claims 1 to 6, characterized in that: The steps include: (1) Weigh each component according to the ratio and mix them evenly; (2) Adding the mixed material to an extruder for blow molding to obtain an environmentally friendly mulch film with high mechanical properties; wherein the temperature of the extruder feeding section is 165-170°C, the temperature of the compression section is 180-200°C, the temperature of the plasticizing section is 180-200°C, and the temperature of the die section is 170-175°C.

Citation Information

Patent Citations

  • Precipitation-resistant high-appearance phosphorus-nitrogen flame-retardant polypropylene composite material and preparation method thereof

    CN115232404A

  • Low-shrinkage polypropylene composite material with excellent mechanical property and preparation method thereof

    CN115637002A

  • Low-odor polypropylene-polyamide alloy material and preparation method thereof

    CN115716959A

  • High-performance graphite oxide reinforced polyethylene composite material and preparation method thereof

    CN103756087A

  • Modified graphene composite polyethylene material and preparation method thereof

    CN110628119A